PROSIDING: Radiation Protection In Medicine Setting the Scene for the Next Decade - P. Ortiz Lópe, Y. Yonekura, T. Knöös, A.L. Wiley, Jr (INTERNATIONAL ATOMIC ENERGY AGENCY, 2015)
medical radiology safety measures congresses radiation